THE INFLUENCE OF FOLLOW-UP INTERNAL AUDIT RECOMMENDATIONS ON THE PERFORMANCE OF PT. JASA RAHARJA (PERSERO) BANDUNG-BRANCH: PENGARUH FOLLOW UP REKOMENDASI AUDIT INTERNAL TERHADAP KINERJA PELAYANAN PT. JASA RAHARJA (PERSERO) CABANG-BANDUNG - Bambang Rismadi (Indonesian Journal of Economy, Business, Entrepreneurship and Finance, 2021)
The purpose of this study was to determine whether there is a significant influence of follow-up recommendations on the performance of internal audit services to PT. Jasa Raharja (Persero) Branch-Bandung, given PT. Jasa Raharja (Persero), Bandung Branch has done a step by entering into an integrated system of Integrated System Services (ISS) in 2009 to facilitate service to the public and be in sync with the police that the acceleration of payment must be faster. The research method used in this research is the descriptive method with a case study approach. The hypothesis was tested with the statistics of the product-moment correlation, coefficient of determination, and the t-test for the significance test. The results of the internal audit report are for the management of PT. Jasa Raharja (Persero) Branch Bandung, in decision-making, the internal auditors' recommendations are expected to assist in achieving organizational goals, especially in the achievement of service performance. With statistical calculation results with 95% confidence level and the error rate of 5% with degrees of freedom df = n2 known for 9.849 t count is more significant than 2.048 in the t table with the following can be concluded there is a significant and positive effect between the follow-up internal audit recommendations on service performance at PT. Rahaja Services (Persero) Branch Bandung and the magnitude of the influence-a follow-up internal audits of service performance is 58.8%.